2013
DOI: 10.1016/j.aquatox.2013.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression and pathologic alterations in juvenile rainbow trout due to chronic dietary TCDD exposure

Abstract: The goal of this project was to use functional genomic methods to identify molecular biomarkers as indicators of the impact of TCDD exposure in rainbow trout. Specifically, we investigated the effects of chronic dietary TCDD exposure on whole juvenile rainbow trout global gene expression associated with histopathological analysis. Juvenile rainbow trout were fed Biodiet starter with TCDD added at 0, 0.1, 1, 10 and 100 ppb (ng TCDD / g food), and fish were sampled from each group at 7, 14, 28 and 42 days (d) af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 56 publications
2
5
0
Order By: Relevance
“…In zebrafish, embryonic exposure to TCDD reduces the number of neurons in the larval brain [50] and causes apoptosis in midbrain [51] . We reported the first evidence of TCDD-induced morphologic lesions in the olfactory organ of rainbow trout [38] , in this study we found similar results from TCDD-treated zebrafish that exhibited highly disorganized and poorly differentiated hyperplastic lamellae ( Figure 5 ). Evidence of TCDD-induced lesions in nasal epithelium of teleost is similar to results in rats which show hyperplastic and metaplastic changes within the nasal mucosa after chronic administration by gavage with TCDD [52] .…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In zebrafish, embryonic exposure to TCDD reduces the number of neurons in the larval brain [50] and causes apoptosis in midbrain [51] . We reported the first evidence of TCDD-induced morphologic lesions in the olfactory organ of rainbow trout [38] , in this study we found similar results from TCDD-treated zebrafish that exhibited highly disorganized and poorly differentiated hyperplastic lamellae ( Figure 5 ). Evidence of TCDD-induced lesions in nasal epithelium of teleost is similar to results in rats which show hyperplastic and metaplastic changes within the nasal mucosa after chronic administration by gavage with TCDD [52] .…”
Section: Discussionsupporting
confidence: 82%
“…In adult fish, TCDD causes hepatic lipidosis and hypertrophy, glycogen depletion in liver, inhibition of fin regeneration and altered gonadogenesis [11], [36], [37]. In juvenile fish, the TCDD-induced lesions observed reflect similarity to exposed embryo/larvae and adults, including craniofacial malformations, degeneration in fin and gill, and altered pigmentation [25], [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…140 Microarray analysis found that genes involved in the immune system processes and immune response to stimuli were the most sensitive potential targets in juvenile rainbow trout fed with TCDD (10 and 100 ng TCDD/g food). 141 Immunologic toxicities such as decreased immune organ mass, lymphoid cell numbers and apoptotic thymocytes were also observed in chicken embryos with PCB-126 exposure. 142,143 Offspring from TCDD-exposed domestic chickens exhibited B cell suppression in their adulthood.…”
Section: Adverse Effects Of Dioxins In Fish Birds and Other Wildlifementioning
confidence: 99%
“…The downregulation was observed for genes encoding for complement factors and for bacterioloytic proteins, such as lysozyme. Likewise, studies on the impact of TCDD on global gene expression in whole body extracts of zebrafish, Danio rerio, and rainbow trout revealed a general downregulation of immune gene transcripts [178,179]. Similarly, liver transcriptomes of fishes exposed to xenobiotic AhR agonists displayed prominent changes in immune pathways (e.g., [180,181]).…”
Section: Immune Transcriptional Responses Of Fish To Ahr-binding Xenobioticsmentioning
confidence: 99%